Perceptual organization and visual attention : inattention, expectation, and Gestalt integration in the visual system - Nobre, Alexandre de Pontes (2020)
Despite decades of investigation, the relationship between attention and perceptual organization is still unclear. It is largely acknowledged that attention is guided by perceptual organization processes; however, the influence of attention on perceptual organization is much less explored. This thesis aimed to investigate how attention influences perceptual organization. Four studies constitute the thesis. In Study 1, we reviewed how Gestalt psychology and the main theories of attention in cognitive psychology and neuroscience relate attention to perceptual organization. This review showed that, although most current theories predict an influence of attention on perceptual organization, there is a gap between theories that explore the heterogeneity in perceptual organization and theories that explore the variety of attentional phenomena. In Study 2, we conducted a meta-analysis of studies investigating implicit processing of unexpected stimuli during inattentional blindness. This review shows considerable evidence for implicit processing of unnoticed stimuli. In Study 3, we attempted to replicate a previous event-related potential (ERP) experiment on implicit texture segregation during inattentional blindness. The results only partially replicate the original study. We discuss possible reasons for these results and relate to the literature on implicit processing during inattentional blindness. In Study 4, we investigate how temporal expectations influence ERPs evoked by stimuli grouped by common-fate. We show that expectation influences common-fate grouping in more than one point in the time course of perception, and that this influence is stronger for more ambiguous stimuli. In the general discussion, the results from the four studies are discussed in relation to the literature on visual attention and perceptual organization.